Peritoneal carcinomatosis of unknown primary site: a case report of metastatic mucinous adenocarcinoma - Vadzim, Nohtseu; Allahudeen, Saarah Dhilfer; Rijwanul Haq, Ibrahim Rasheed (International Surgery Journal, 2026)
Metastatic mucinous adenocarcinoma, a distinct subtype associated with extensive mucin production presents diagnostic and therapeutic challenges. This case involves a 21-year-old male with high-grade mucinous adenocarcinoma manifesting as cancer of unknown primary site, characterized by widespread peritoneal carcinomatosis and rapid progression despite systemic chemotherapy. The tumor’s aggressive behavior and thromboembolic complications underscore the need for tailored, multidisciplinary management strategies.